این میری شمل اسلام اور مشرق: Annemarie Schimmel: Islam and East (Research Journal Tahqeeqat, 2025)
Annemarie Schimmel, an eminent German academic, was a scholar who was passionate about the study of Islamic culture, Sufism, and Eastern philosophy throughout her lifetime. The Easterners never considered Islam to be any single thing, rather they had seen it as a diversity-oriented interaction. It is something material and something transcendent. It was probably the most outstanding Islamicist Annemarie Schimmel who made research in the field of the linkage of Islamic traditions with the cultures of the East, and noted that both of them were the inputs into literature, art and mysticism. As her work amply demonstrates, the development of thought on Sufism and poetry was greatly under the influence of Persians, Indians and Central Asians. Such contacts enriched the spiritual and cultural pluralism of Islam, initiating a process of creative amalgamation. The work of Schimmel positions the scope of this interaction within the corpus of orthodoxies of an elaborately factured intellectual and artistic creations that traversed nations and epochs in the increase of fellowship across boundaries.